Prevalence and Associated Factors of Depression among Admitted Adult Patients in Surgical and Medical Wards of Saint Paul's Hospital Millennium Medical College, Addis Ababa, Ethiopia. (31st January 2021) - Siyoum, Merga; Assfaw, Getachew; Yitbark, Henok; Tesfaw, Getachew
Abstract : Background . Depression is a leading cause of major public health problems globally, and its prevalence has been increasing, particularly in low- and middle-income countries including our country. Therefore, this study is aimed at exploring depression symptoms and their determinants among admitted medical and surgical patients which is important to get optimal care for patients. Methods . An institution-based cross-sectional study was conducted from May to June 2019, on adults' medical and surgical admitted patients at Saint Paul's Hospital Millennium Medical College, Addis Ababa, Ethiopia. The systematic random sampling technique was used to get a total of 590 samples. The standardized hospital anxiety and depression scale (HADS) was used to assess individual depression symptoms. We computed the bivariate and multivariate binary logistic regression analyses to identify factors associated with depression symptoms. Statistical significance was declared at P < 0.05 . Result . The prevalence of depression symptoms was found to be 53.9% (95% CI: 50.2, 57.0). In the multivariable logistic regression, female sex (AOR = 2.04, 95% CI: 1.35, 3.09), being single (AOR = 3.65, 95% CI: 3.48, 2.10, 5.78), widowed (AOR = 2.82, 95% CI: 1.27, 6.30), unable to read and write (AOR = 2.71, 95% CI: 1.14, 6.47), admission at medical ward (AOR = 1.59, 95% CI: 1.02, 2.46), history of mental illness (AOR = 1.59, 95% CI: 1.02, 2.46), and poor social support (AOR = 2.82, 95% CI: 1.57, 5.11) were factors significantly associated with depression symptoms. Conclusion . The prevalence of depression symptoms among admitted patients was high. Female sex, being single, widowed, unable to read and write, admission at medical ward, history of mental illness, and poor social support were factors significantly associated with depression symptoms. It is better for the Ministry of Health to give training on how to screen depression among medical and surgical patients, and interventions that would be addressing the awareness of the above factors would be beneficial to prevent further complications.